Program Pendampingan Hidup Sehat bagi Diabetesi di Posbindu Kelurahan Sumber Jaya Kecamatan Kampung Melayu Kota Bengkulu - Sari, Nengke Puspita; Sari, Maritta; Iskandar, Siska; Indaryani, Indaryani; Sulastri, Weni; Utami, Rizka Wahyu; Darma, Dimas Dewa; Sutriyani, Sutriyani (Gayaku Publisher, 2024)
Padang Serai Community Health Center data for 2023 shows that there are 56 residents suffering from diabetes mellitus (DM) and 20 residents classified as prediabetic based on the results of monthly fasting blood sugar checks. Based on these problems, community service (PKM) was carried out in the form of a Healthy Living Assistance Program with the aim of providing motivation to residents to adopt a healthy lifestyle. Program activities are divided into three stages, namely: program socialization including how to fill out a healthy living logbook, education via WhatsApp groups, and evaluation. Before and after participating in the program, residents' health parameters were measured. Residents' implementation of a healthy lifestyle is evaluated based on logbook recording. The program activities, which lasted for 3 weeks, were attended by residents, most of whom were mothers with a body mass index classified as obese. The PKM results showed that after implementing a healthy lifestyle there was an improvement in health parameters, namely a decrease in fasting blood sugar levels, total cholesterol, blood pressure and body weight. It can be concluded that the Healthy Living Assistance Program has succeeded in encouraging residents to live healthily in preventing and controlling DM